Clinical Pharmacist Counselling Improves Long-term Medication Safety and Patient-reported Outcomes in Anti-TNF-treated Patients With Inflammatory Bowel Diseases: The Prospective, Randomized AdPhaNCED Trial. - Plechschmidt, Johannes; Fietkau, Konstantin; Hepp, Tobias; Dietrich, Peter; Fischer, Sarah; Krebs, Sabine; Neurath, Markus; Dörje, Frank; Atreya, Raja (Inflammatory Bowel Diseases, 2025)
BACKGROUND: Antitumor necrosis factor (anti-TNF) antibody treatment has led to marked improvements in the management of patients with inflammatory bowel diseases (IBDs). Nevertheless, anti-TNF therapy is associated with potential adverse drug reactions (ADRs). Our prospective, randomized trial investigated the effect of intensified clinical pharmacist counselling in a multidisciplinary team on medication safety in anti-TNF-treated IBD patients. METHODS: Patients with IBD with ongoing anti-TNF treatment were enrolled in our tertiary center AdPhaNCED trial and randomized to either receive conventional standard of care (control group) or additional clinical pharmacist counselling (intervention group) over 12 months. The primary end point consisted of the number and severity of ADRs associated with anti-TNF therapy. Secondary end points included patient satisfaction with medication information and medication safety. RESULTS: One hundred twenty-seven IBD patients were included in this study. Anti-TNF-related ADRs were significantly lower in the intervention compared with the control group (0.20 vs 0.32 [mean] ADR/patient/month, P = .006) after 12 months. The risk of more severe ADRs (Common Terminology Criteria for Adverse Events [CTCAE] grade ≥2) was significantly higher in the control compared with the intervention group (hazard ratio, 0.34; P = .001). The probability of ADR resolution (hazard ratio, 2.02; P < .001) and patient satisfaction with medication information (14.82 vs 11.60; P < .001) were significantly higher in the intervention group compared with the control group. CONCLUSIONS: Our study results demonstrate that intensified pharmacist counselling significantly reduces the occurrence and severity of therapy-related ADRs and improves patient satisfaction. Clinical pharmacists should therefore be part of a holistic approach to IBD care delivered by a multidisciplinary team.
EVALuna2:566019
Keywords: inflammatory bowel diseases; patient reported outcomes; adverse drug reaction management; medication safety; patient support program